2008
DOI: 10.1002/ejlt.200800100
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of enzymatic interesterification in the oils and fats industry

Abstract: Immobilised lipases have now become accepted as a mainstream technology for fat modification. This paper presents the development of this technology in particular for the production of trans-free fats. One of the factors influencing this development has been concern for health, which has made trans fats a major issue for food manufacturers and consumers. Enzymatic interesterification is a relatively new method for producing trans-free alternatives for fats used in conventional margarines and shortenings. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 20 publications
1
44
0
2
Order By: Relevance
“…I continued my letter by explaining how analytical mistakes were responsible for this 'proof ' and concluded that the article should never have been published. -I do not mind articles being subjective because research itself is a subjective activity, but I object to articles being biased, or even misleading for commercial reasons and that is how I would characterise the comparison between the chemically catalysed and the enzymatically catalysed interesterification in an otherwise excellent article [63]. Moreover, when these biased statements are repeated often enough, they start to lead a life of their own and tend to be no longer questioned.…”
Section: Discussionmentioning
confidence: 96%
“…I continued my letter by explaining how analytical mistakes were responsible for this 'proof ' and concluded that the article should never have been published. -I do not mind articles being subjective because research itself is a subjective activity, but I object to articles being biased, or even misleading for commercial reasons and that is how I would characterise the comparison between the chemically catalysed and the enzymatically catalysed interesterification in an otherwise excellent article [63]. Moreover, when these biased statements are repeated often enough, they start to lead a life of their own and tend to be no longer questioned.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand the enzymatic process is much simpler and carried out in a fixed-bed reactor under mild conditions. The end-product is ready to be deodorized without purification 64 .…”
Section: Intraesteri Ed Fatmentioning
confidence: 99%
“…od pozyskania i przetwarzania surowca przez proces produkcyjny, dystrybucję, ostateczne użytkowanie i utylizację odpadów. Technika LCA jest głów-nie wykorzystywana do porównywania wpływu na środowisko dwóch lub więcej alternatywnych procesów zapewniających takie same korzyści [Holm, Cowan 2008].…”
Section: Biodiesel Jako Ekologiczny Zamiennik Oleju Napędowegounclassified